Substrate-Flexible Two-Stage Fed-Batch Cultivations for the Production of the PHA Copolymer P(HB-co-HHx) With Cupriavidus necator Re2058/pCB113 - Santolin, Lara; Waldburger, Saskia; Neubauer, Peter; Riedel, Sebastian L. (Frontiers in Bioengineering and Biotechnology, 2021)
Recent studies of the impact and dimension of plastic pollution have drawn the attention to finding more sustainable alternatives to fossil-based plastics. Microbially produced polyhydroxyalkanoates (PHAs) biopolymers are strong candidates to replace conventional plastic materials, due to their true biodegradability and versatile properties. However, widespread use of these polymers is still hindered by their high cost of production. In the present study, we target high yields of the PHA copolymer poly(hydroxybutyrate-co-hydroxyhexanoate) [P(HB-co-HHx)] using a substrate-flexible two-stage fed-batch approach for the cultivation of the recombinant Cupriavidus necator strain Re2058/pCB113. A more substrate flexible process allows to cope with constant price fluctuations and discontinuous supply of feedstocks at the market. Utilizing fructose for biomass accumulation and rapeseed oil for polymer production resulted in a final biomass concentration of 124 g L-1 with a polymer content of 86 wt% holding 17 mol% of HHx. Productivities were further optimized by operating the biomass accumulation stage in a “drain and fill” modus where 10% of the culture broth was recycled for semi-continuous biomass accumulation, after transferring 90% to a second bioreactor for PHA production. This strategy succeeded in shortening process times rising productivity yields to ~1.45 g L-1 h-1.